Gambaran Hematologi pada Defisiensi Vitamin B12 - Irena Ujianti (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2021)
Background and Aims. Anemia is a condition when the number of red blood cells or hemoglobin is lower than the normal number. The main cause of anemia is a lack of factors for the formation and maturation of red blood cells. Vitamin B12 plays a role in the synthesis and maturation of red blood cells, a lack of this vitamin will cause the formation and maturation of red blood cells to be disrupted. Method. This was an experimental animal study with twelve rats with frederer's family. The rat was fed a Vitamin B12 Deficient Diet for 16 weeks as the treatment group and standard diet as the control group. Vitamin B12 in the liver was analyzed in rats for 16 weeks. Hemoglobin and MCV were analyzed in plasma for 16 weeks. Results are expressed as means of control, and test animals were established by ANOVA using SPSS 20.0 software Results. In the present study, we found that liver vitamin B12 level was decreased in treatments groups compares to the positive control group at sixteen weeks (p<0.01). Hemoglobin was decreased in the treatment group compare positive control group at sixteen weeks (p<0.001). Mean Corpuscular Volume (MCV) was increased in the treatment group's compare positive control group at sixteen weeks (p<0.01) Conclusions. Our findings demonstrate that vitamin B12 deficiency decreased hemoglobin and increased MCV.